AMSSM Scientific Statement Concerning Viscosupplementation Injections for Knee Osteoarthritis: Importance for Individual Patient Outcomes. Issue 1 (January 2016) - Trojian, Thomas H.; Concoff, Andrew L.; Joy, Susan M.; Hatzenbuehler, John R.; Saulsberry, Whitney J.; Coleman, Craig I.
Abstract : Objective: Osteoarthritis (OA) is a disabling disease that produces severe morbidity reducing physical activity. Our position statement on treatment of knee OA with viscosupplementation injection [hyaluronic acid (HA)] versus steroid [intra-articular corticosteroid (IAS)] and placebo [intra-articular placebo (IAP)] is based on the evaluation of treatment effect by examining the number of subjects within a treatment arm that met the Outcome Measures in Rheumatoid Arthritis Clinical Trials–Osteoarthritis Research Society International (OMERACT-OARSI) criteria, which is different and more relevant than methods used in other reviews which examined if the average change across the treatment groups was clinically different. Data Sources: We performed a systematic literature search for all relevant articles from 1960 to August 2014 in the MEDLINE, EMBASE, and Cochrane CENTRAL. We performed a network meta-analysis (NMA) of the relevant literature to determine if there is a benefit from HA as compared with IAS and IAP. Main Results: Eleven articles met the inclusion criteria from the search strategy. On NMA, those subjects receiving HA were 15% and 11% more likely to respond to treatment by the OMERACT-OARSI criteria than those receiving IAS or IAP, respectively ( P < 0.05 for both). Conclusions: In light of the aforementioned results of our NMA, the American Medical Society for Sport Medicine recommends the use of HA for the appropriate patients with knee OA.